THEATRICAL PERFORMANCE IMIGRAN DALAM POISSON DâOR KARYA LE CLÃZIO - , PARYATUN ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to reveal the theatrical performance of immigrants in Poisson d'or, a novel written by Le Clézio. The context of theatrical performance relates to several issues. First, the efforts are undertaken by immigrants to survive in the migration country by doing a theatrical performance. Therefore, it is necessary to know about the forms of theatrical performance as an immigrantsâ political identity, which is an effort to show his theatrical performance in order to adapt, negotiate or resist. Second, the relations between the core community subjects and the immigrants provides in Poisson d'or. Third, theatrical performances are seen in the sociocultural context of French society. Erving Goffman dramaturgy theory is applied related to the theatrical performances. Besides, this study is also used the francophone literature perspective, postcolonial literature, and identity politics. Roland Barthesâ method of semiotics focusing on myth is as the method of analyzing data. The result of the study reveals that the immigrants make efforts of theatrical performance by doing varied ways on the side of the front stage and the back stage as well. In the front stage, the immigrants have built positive images for they are dealing directly with the core community by coding, including using costumes, body language, maturity of thought, identity as an African people, appearance, hobbies, intelligence, lifestyle, and linguistic abilities. In the back stage, the immigrants have made the back stage area as a hidden realm that supports the creation of positive images at the front stage e.g. through freedom, insulting words, and inferiority. The relations existing between the immigrants and the core society is hierarchical and equal relations. In the hierarchical relation, there are relations of the dominants and dominated people, employer and employee, parents and adopted children, teachers and pupils, and the punished and the Punisher. There is an equal relation among immigrants and African people. The reading of theatrical performance in sociocultural context of Africa nation reveals that theatrical performance in novel have the homology with theatrical performance in sociocultural context, however there is no homology because there is no such phenomenons in novel or conversely. The reality shows that France as a respected country in the world releases policies that are not pro-immigrant, such as prohibition veil wearing, or restricting the immigrants into the French national football team. Thus, theatrical performance strategy became important for immigrants in order to gain more space and to be acknowledged.